REDISCOVERING SYMBOLISM IN CHRISTIAN AND ASIAN CULTURES - Rahme, Chady (Asian Horizons, 2013)
Underneath the joys, hopes griefs and anxieties of human beings, lies a common desire, which is the human desire to always go beyond. We want to go beyond our sufferings, beyond our fears, which mainly come from the finiteness that we keep on encountering in this world. We also want to go beyond our temporary joys, seeking joys that do not end, not limited or threatened by finiteness. Here lies the main source of our anxieties, the main challenge in our human condition.